(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Understanding of diversity, and associations in it, especially reef fish, is very important in the framework of sustainable management. The purpose of this study is to examine the community structure and its similarity based on family abundance of reef fishes and the lifeform. Retrieval of lifeform data using the Point Intercept Transect method, and collection of reef fishes data using the Underwater Visual Census method. Correspondence Analysis is used to describe the similarity of the abundance of reef fishes families and lifeforms to reef profile. The results showed that the total number of reef fish found for indicator fish and targeted fish at 3,666 individuals consisting of 130 species from 26 families, abundance of individuals of the highest target fishes at Tanah Merah Cape, Harlem Cape, Kwahkeboh Island, Sarebo Cape, Amayepa, Amay Cape and Kuburan Tablasufa Cape. Diversity (H’) is relatively high, which is around 2.66-3.63, the Similarity Index (E) is quite high, which ranges from 0.55 to 0.76 (→1), and the Dominance Index (D) is low which ranges 0.03-0.08 (→0). The abundance of reef fishes families and lifeform has similarity to reef profiles.